Absence of Wip1 partially rescues Atm deficiency phenotypes in mice - Darlington, Yolanda (2011)
Wildtype p53-Induced Phosphatase 1 (WIP1) is a serine/threonine phosphatase that dephosphorylates proteins in the ataxia telangiectasia mutated (ATM)-initiated DNA damage response pathway. WIP1 may play a homeostatic role in ATM signaling by returning the cell to a normal pre-stress state following completion of DNA repair. To better understand the effects of WIP1 on ATM signaling, we crossed Atm-deficient mice to Wip1-deficient mice and characterized phenotypes of the double knockout progeny. We hypothesized that the absence of Wip1 might rescue Atm deficiency phenotypes. Atm null mice, like ATM-deficient humans with the inherited syndrome ataxia telangiectasia, exhibit radiation sensitivity, fertility defects, and are T-cell lymphoma prone. Most double knockout mice were largely protected from lymphoma development and had a greatly extended lifespan compared to Atm null mice. Double knockout mice had increased p53 and H2AX phosphorylation and p21 expression compared to their Atm null counterparts, indicating enhanced p53 and DNA damage responses. Additionally, double knockout splenocytes displayed reduced chromosomal instability compared to Atm null mice. Finally, doubly null mice were partially rescued from infertility defects observed in Atm null mice. These results indicate that inhibition of WIP1 may represent a useful strategy for cancer treatment in general and A-T patients in particular.